Administrative violence, prison geographies and the photographs of Tuol Sleng Security Center, Cambodia. Issue 4 (7th July 2014) - Tyner, James A; Devadoss, Christabel
<x xml:space="preserve">Abstract</x> During the Cambodian genocide, between 1975 and 1979, approximately 200 security centres were established by the Khmer Rouge. One of these prisons, designated by the code‐name S‐21, was responsible primarily for the punishment of individuals 'guilty' of committing state crimes. During their detainment at S‐21 prisoners were documented, photographed, interrogated and tortured before ultimately being executed. Following the downfall of the Khmer Rouge, the photographs of S‐21 have received considerable attention, notably as evidence of crimes against humanity and as a means of discussing the ethics of post‐mortem photographs. Less attention has considered the photographs as a means of furthering our understanding of the administrative violence of the genocide itself. Through a case study of the material practice of photography at S‐21 we examine the inner logics of administrative violence. Specifically, we detail how photographs literally and symbolically expose law‐making and law‐preserving violence. The first part of our paper provides an overview of post‐conflict administrative violence; this is followed with a discussion of security systems under the Khmer Rouge and an examination of the violence of photography. In so doing we contribute to the literatures on prison geographies and geographies of violence.